2020
DOI: 10.1530/ec-19-0467
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic benefits of different bariatric operations: what procedure to choose?

Abstract: Bariatric surgery is established as a highly effective treatment for obesity and related metabolic complications. Although once seen as a last resort for patients with obesity, given the data demonstrating the profound weight loss, improvement in comorbidity and safety, perceptions have since shifted. There is evidence from 12 RCTs demonstrating its safety and efficacy in terms of weight loss which is sustained in the long term with a resultant improvement in co-morbidity. Clinicians are increasingly recognisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…Nowadays, bariatric surgery is the most efficient method of obesity treatment [12]. Many studies have shown that bariatric surgery not only helps patients achieve long-term weight loss but also removes obesity-related complications, including T2DM and high blood pressure [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, bariatric surgery is the most efficient method of obesity treatment [12]. Many studies have shown that bariatric surgery not only helps patients achieve long-term weight loss but also removes obesity-related complications, including T2DM and high blood pressure [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 It is known that bariatric surgery is a safe, effective treatment that is indicated in people with morbid obesity and type II obesity with associated serious comorbidities, such as type 2 diabetes mellitus (DM2), arterial hypertension (HTN) or obstructive sleep apnea (OSA). 8 , 9 Therefore, bariatric surgery should be included in the structured waiting lists with the commitment of the autonomous communities to guarantee a delay of no more than 6 months, as is done with other benign surgical pathologies. 10 …”
Section: Bariatric Surgery In the Context Of Sars-cov-2mentioning
confidence: 99%
“…It is also insufficient in patients with morbid obesity (body mass index (BMI) > 40 kg/m 2 ). Thus, the most effective method of treatment for morbid obesity is bariatric surgery [9]. Of the many surgical techniques, the most popular bariatric procedures are sleeve gastrectomy and Roux-en-Y gastric bypass [10].…”
Section: Introductionmentioning
confidence: 99%